Buy coal to mitigate climate damage and benefit from strategic deposit action - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2015)
In the world economy with interdependent markets for fossil fuel and deposits, some coalition of countries fights climate change by purchasing and preserving fossil fuel deposits, which would be exploited otherwise. If the coalition's policy parameters are the demand and supply of deposits (deposit policy), the outcome is inefficient, but the coalition is better off with than without exerting market power by influencing prices in its own favor. In the special case, in which noncoalition countries do not suffer from climate damage, the outcome is efficient if the coalition is a price taker on both markets, but inefficient otherwise. The latter result demonstrates that Harstad's (2012, Theorem 1) efficiency result is not robust with respect to variations in the concepts of deposit market and strategic behavior. We also analyze a policy where the coalition's first policy parameter is its deposit demand, as before, and the second policy parameter is fuel supply rather than deposit supply. That policy turns out to be equivalent to the deposit policy (as defined above) under some conditions but non-equivalent under others.
Keywords: Q31; Q38; Q55; 330; climate coalition; fossil fuel; deposits; extraction; deposit policy